A night-lighting technique for capturing peruvian thick-knees (Burhinus superciliaris) and first data on molt sequence and biometrics - Camacho, Carlos; Torres, Santiago (Instituto de Ecología, A.C., 2015)
The Peruvian thick-knee Burhinus superciliaris (Tschudi, 1843) is an uncommon species with highly cryptic behavior, and is thus difficult to capture and monitor. As a result, many questions remain about their basic life-history strategies and conservation status. During January and February 2009, a night-lighting technique was developed for the selective capture of Peruvian Thick-knees in southwestern Ecuador, and the molt sequence and biometrics of freeranging individuals were documented for the first time. Birds were located (24 sightings) and captured (four individuals) along 48 km of unpaved roads using a lightweight LED flashlight and a 80-cm diameter hand-held net. On average, capture success was 0.29 birds captured/session (range, 0–2) out of 0.64 attempts per session (range, 0–4) and a capture rate of 0.44 birds/attempt (n = 9 attempts). The molt progress was sequential and highly symmetrical and no simultaneous growing of feathers from the same feather tract was observed, except in secondaries. In contrast to the rectrices, primary feathers were shed from the innermost to the outermost, whereas birds seemed to have two molting centers for secondaries. The high recapture opportunities of this method allows monitoring the molt sequence, weight gain, spatial use and other life-history parameters of the Peruvian Thick-knee and possibly other small and medium-sized birds.